Antiapoptotic role of the p38 mitogen-activated protein kinase–myocyte enhancer factor 2 transcription factor pathway during neuronal differentiation - Okamoto, Shu-ichi (The National Academy of Sciences, 2000)
Myocyte enhancer factor 2 (MEF2) is in the MADS (MCM1agamous-deficiens-serum response factor) family of transcription factors. Although MEF2 is known as a myogenic factor, the expression pattern of the MEF2 family of genes (MEF2A-D) in developing brain also suggests a role in neurogenesis. Here we show that transfection with MEF2C, the predominant form in mammalian cerebral cortex, induces a mixed neuronal/myogenic phenotype in undifferentiated P19 precursor cells. During retinoic acid-induced neurogenesis of these cells, a dominant negative form of MEF2 enhances apoptosis but does not affect cell division. The mitogen-activated protein kinase p38α activates MEF2C. Dominant negative p38α also enhances apoptotic death of differentiating neurons, but these cells can be rescued from apoptosis by coexpression of constitutively active MEF2C. These findings suggest that the p38α/MEF2 pathway prevents cell death during neuronal differentiation.